Design and Analysis of an Extruder for Bio-Composite Filament Fabrication - Vinodhkumar, R.; Sekar, T.; Nandakumar, N. (Journal of Electronics and Informatics, 2022)
Fused Deposition Modelling (FDM) or Fused Filament Fabrication (FFF) is an additive manufacturing technique in which layers of materials are fused together in a pattern to form an item. Acrylonitrile Butadiene Styrene (ABS), Poly Lactic Acid (PLA), Poly Ethylene Terephthalate (PET), Poly Vinyl Alcohol (PVA), Sandstone, and other materials are utilised in this FDM 3D printer. However, the rapid changes of Global needs and advances in Engineering domain, are in need of the combination of new materials to cater to fulfil the society and technical demands. Therefore, this work attempts to develop a new bio-composite filament for making components, which are associated with medical application. The commercially available extruders are not so cost effective and custom based for the biomaterials chosen for this work. The selected materials for making the bio-composite are Poly Lactic Acid (PLA), Ultra High Molecular Weight Poly Ethylene (UHMWPE) along with Cissus quadrangularis (Adamant creeper) powder. So, it is essential to design and develop an extruder indigenously to make the Bio-composite filament. For this first phase, the basic components of the customized designed extruder are modelled using Solidworks 2018 and assembled. Subsequently the usage viability analysis is done by using ANSYS 18.1 at Manufacturing Engineering CAD laboratory. The thermal and dynamic analysis are successfully carried out. The results reveal that the heat sink of extruder could withstand up to 300C and the heat transfer rates are reported.
Keywords: Fused Deposition Modelling; Poly Lactic Acid; Ultra High Molecular Weight Poly Ethylene; Cissus quadrangularis